Building capacity for sustainable, scalable, place-based youth crime prevention - Homel, Ross (Frontiers in developmental and life-course criminology, 2024)
The primary prevention of youth crime is not a prominent feature of crime policies in Australia or internationally. We argue that to achieve sustained impact on youth crime at a whole-of-community or national level government decision-makers must encourage the formation of “intermediary spaces” that link through respectful relationships the worlds of science and service. We focus on new forms of human capital and technological infrastructure that by being grounded in developmental research and embedded in government place-based programmes furnish frontline professionals with tools and supportive arrangements that make more likely both the translation of scientific findings into routine service delivery and the incorporation of lived experience into developmental science. We highlight Communities That Care (CTC), a community-based prevention system developed outside of government that is grounded in developmental theory and research, arguing that it provides proof-of-concept for this model for achieving sustained impact on youth crime at scale. The CTC approach should therefore be central to place-based collective impact initiatives but because it has not been incorporated into public systems it has struggled to achieve scale. To address this challenge, we worked in the CREATE Project within a well-established federally funded programme, Communities for Children, which aims to increase the wellbeing of children aged 0–12 years in 52 disadvantaged communities. We adapted the CTC methodology to construct a range of new online measures and support systems, the use of which was mediated by skilled “boundary spanners” called Collective Change Facilitators. However, CREATE faces similar policy resistance as CTC, suggesting a lack of accountability by decision-makers at multiple levels for the achievement through place-based initiatives of measurable population-level reductions in youth crime and improvements in child wellbeing. These policy barriers may however be steadily overcome if DLC researchers and prevention scientists can accumulate further evidence for impact on youth outcomes through innovations in translational or intermediary systems tailored to communities’ needs.